Matrična generalizacija difuzijske enačbe: raziskovanje prepleta difuzije delcev in toplote - Mravlje, Jernej (Matrika, 2024)
When the thermoelectric phenomenon in solid is not negligible, the transport of charge and heat are mutually connected. This also influences the diffusion, requiring it to be formulated in matrix form in this case. The elements of the diffusion matrix are linked to transport coefficients, resulting in a generalized Nernst-Einstein relation. The off-diagonal element, which determines the strength of coupling between charge and heat diffusion, is determined by the difference between the Seebeck coefficient and its Kelvin approximation.
Keywords: charge diffusion; diffusion; difuzija; heat diffusion; transport naboja; transport toplote